2016
DOI: 10.1002/wrna.1386
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles and context of circular RNAs

Abstract: Circular RNAs (CircRNAs) represent a large class of noncoding RNAs (ncRNAs) that have recently emerged as regulators of gene expression. They have been shown to suppress microRNAs, thereby increasing the translation and stability of targets of such microRNAs. In this review, we discuss the emerging functions of circRNAs, including RNA transcription, splicing, turnover, and translation. We also discuss other possible facets of circRNAs that can influence their function depending on the cell context, such as cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 61 publications
0
123
0
Order By: Relevance
“…Here, we have used a combination approach and identified 133 extracellular circRNAs (ex‐circRNAs) and further validated age‐related changes in three different ex‐circRNAs: circ_1305 , circ_722, and circ_1445 . Emerging data suggest that circRNAs can function to sponge miRNAs and RBPs (Panda, Grammatikakis, Munk, Gorospe & Abdelmohsen, 2017). Here, we have identified several serum miRNAs that are predicted to bind to the ex‐circRNAs and also with several RBPs.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have used a combination approach and identified 133 extracellular circRNAs (ex‐circRNAs) and further validated age‐related changes in three different ex‐circRNAs: circ_1305 , circ_722, and circ_1445 . Emerging data suggest that circRNAs can function to sponge miRNAs and RBPs (Panda, Grammatikakis, Munk, Gorospe & Abdelmohsen, 2017). Here, we have identified several serum miRNAs that are predicted to bind to the ex‐circRNAs and also with several RBPs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Karreth et al [5] reported that miR-653, miR-134, and miR543 mediated the effect of BRAFP1 on BRAF expression and MAPK activation. Li et al [6] also found that miR-7, miR-17, and miR-214 could mediate the regulation of circ-ITCH in inhibiting esophageal squamous cell carcinoma development by suppressing the Wnt/β-catenin pathway. Therefore, exploring the functions of miRNAs could provide novel insights to identify the mechanisms underlying disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Intronic circRNAs consist of lariat introns. Exonintron circRNAs contain both exons and introns [16,18]. Mounting evidence indicates that circRNAs could be free from RNase R digestion to protect the special circular construction and thus are more stable than linear mRNAs, possibly explaining their long half-lives [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of circRNAs hiding translation start sites could impede the translation of residual linear transcripts, referred to as the "mRNA trap," indicating the competition of circRNAs with pre-mRNAs of their host genes [15,25]. Additionally, circRNAs exert regulatory effects by binding to lncRNAs, transcription factors, and RNA-binding proteins, which, at the same time, results in feedback behavior on circRNA stability, abundance, and/or localization [16,26]. In aggregate, the mechanisms by which circRNAs modulate gene expression are intricate and variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation